The predictive capacity of the Glasgow-Blatchford score for the risk stratification of upper gastrointestinal bleeding in an emergency department - José Manuel Recio-Ramírez (Revista Espanola de Enfermedades Digestivas, 2015)
Objectives: To assess the ability of the Glasgow Blatchford Score (GBS) system to identify the need for urgent upper gastrointestinal endoscopy (UGIE) in patients with upper gastrointestinal bleeding (UGIB). Methods: An observational, retrospective study was carried out in all patients attended at the ER for suspected UGIB in one year. Patients were split into two categories -high-risk (>2) and low-risk (≤2)- by means of the GBS system. Results: A total of 60 patients were included. Of these, 46 were classified as "high-risk" (> 2) and 14 as "low-risk" (≤ 2) subjects. The characteristics of patients in the low-risk group included: Mean age: 46.6 ± 13.7 (18-88) years. Males/females: 7/7. Urgent endoscopy revealed: normal (50%; n = 7); esophagitis (21.4%; n = 3); gastritis (14.2%; n = 2); Mallory-Weiss syndrome (7.1%; n = 1); non-bleeding varices (7.1%; n = 1). The characteristics of patients in the high-risk group included: Mean age: 68.7 ± 19.8 (31-91) years. Males/females: 30/16. Digestive endoscopy revealed: Gastric/duodenal ulcer (56.52%; n = 26); normal (17.39%; n = 8); esophagitis (8.69%; n = 4); gastritis (8.69%; n = 4); angioectasia (4.34%; n = 2); bleeding varices (4.34%; n = 2). Low-risk patients exhibited no lesions requiring urgent management during endoscopy, and the sensitivity of the GBS scale for high-risk UGIB detection was found to be 100% (95% CI: 86.27%, 99.71%), with a specificity of 48.28% (95% CI: 29.89, 67.1%). Conclusions: The GBS scale seems to accurately identify patients with low-risk UGIB, who may be managed on an outpatient basis and undergo delayed upper GI endoscopy at the outpatient clinic.